A comparative study on the bottleneck pedestrian flow under different movement motivations. (March 2021) - Li, Hongliu; Zhang, Jun; Song, Weiguo; Yuen, Kwok Kit Richard
Abstract: Understanding movement characteristics of high-motivated pedestrians passing through bottlenecks in buildings is of great help to improve the safety levels of pedestrians especially in fire or other emergencies. In this study, an experiment is performed to compare the movement characteristics of high and low motivated pedestrians passing through bottlenecks with different widths. Voronoi Diagram based methods are applied to obtain the precise density, speed and other parameters. Refer to the density distribution over space, we observe arch-like shape of the high motivated pedestrians and tear-drop shape of low motivated pedestrians. The relation between flow and bottleneck width is normalized by excluding the influence from the body dimensions and movement motivations. Deviation angle of pedestrians are Gauss distributed and the range narrows with the increasing individual speed. Highlights: We compare pedestrian bottleneck flows under high and low motivations based on controlled experiment. Arch- and teardrop-shape spatial distributions of the density are observed for different motivations. We obtain the normalized relations between flow and bottleneck width from different experiments. Queuing time in front of the bottleneck shows a downward trend with the increasing bottleneck widths. Deviation angles are Gauss distributed for pedestrians in the upstream of the bottleneck.